Identification and Genetic Diversity Analysis of Cinnamomum parthenoxylon (Jack) Meisn Species in Song Hinh Protection Forest, Vietnam Based on Three Chloroplast Gene Regions - Dinh Duy Vu; Mai Phuong Pham; Ngoc Huyen Dang; Xuan Dac Le; Hung Cuong Dang; Huu Thuc Nguyen; Dang Hoi Nguyen (Biomedical and Biotechnology Research Journal)
Background: Cinnamomum parthenoxylon is an important component of tropical Vietnam and has major ecological and economic significance, which has been threatened in recent decades due to the destruction of its habitat and overexploitation. Methods: In the present study, first, three chloroplast DNA (cpDNA) regions (matK, rbcL, and trnH-psbA) were initially examined to identify C. parthenoxylon species using Maximum Likelihood (ML). Then, genetic diversity analysis of C. parthenoxylon species in the Song Hinh protection forest, Phu Yen Province, Vietnam. Results: The nucleotide sequences of matK, rbcL, and trnH-psbA were determined to be 786bp, 513bp, and 464bp, respectively. The novel sequences have been deposited in Genbank with matK (PQ106670-PQ106689), rbcL (PQ106690-PQ106709), and trnH-psbA (PQ1066710-PQ106729). The analysis revealed that the mean base compositions of matK, rbcL, and trnH-psbA were nucleotide T (34.8%, 28.3%, and 30.4%), C (19.4%, 22.5%, and 15.1%), A (29.1%, 26.6%, and 39.8%), and G (16.7%, 22.7%, and 14.7%), respectively. In each of the three cpDNA regions, the GC content was discovered to be significantly lower than the AT content. According to ML phylogenetic analyses, all samples in the Song Hinh protection forest are closely related to C. parthenoxylon in GenBank, with robust supporting values. Moreover, only 0.25% (2 haplotypes) of the sequences showed polymorphism in the matK region, whereas 0.78% (4 haplotypes) in the rbcL region. The most variable trnH-psbA (3.44%) (16 haplotypes) intergenic region was the most useful genetic diversity analysis of C. parthenoxylon. The genetic variations in C. parthenoxylon were moderate, with an average number of nucleotide differences (Kt = 1.042–4.984), haplotype diversity (Hd = 0.521–0.916), and nucleotide diversity (Pi = 1.33–10.74 × 10–3). Conclusions: The results of this study have the potential to provide valuable information that is essential for the classification, and identification of the plant’s origin, propagation, and conservation program of C. parthenoxylon in Vietnam.